Clinicopathological Study of Urinary Bladder Cancer - Garalla , Hanan M; Darraz , Khaled M (Scientific Journal of University of Benghazi, 2022)
Background: The histologic classification of bladder tumors remains an important predictor of treatment response and patient outcome. Aim: The present study aimed to see the histomorphological pattern of urinary bladder cancer (UBC) with regard to age and sex, and to determine the stage, grade, and the presence of muscle invasion. Methods: A six-year retrospective study of all consecutive cases diagnosed in the Department of Pathology, Faculty of Medicine (2006-2011), and Department of Urology, Faculty of Medicine, Benghazi Libya (2019-2020). Results: The study included 120 patients. The ages ranged from 18-96 years old with a median of 67.5 years. 90% were males and 10% were females giving a male to female ratio of 9:1. Transitional Cell Carcinoma (TCC) was the predominant histological type 100 (83.3%), followed by Squamous Cell Carcinoma (SCC) 20 (16.7%). Grade II of urinary bladder cancer was the most common tumor grade accounting for 77 (64.2%). 98 (81.7%) of the patients had Non-Muscle Invasive Bladder Cancer (NMIBC) versus 22 (18.3%) who had Muscle Invasive Bladder Cancer (MIBC). Pathological staging showed that 33 (27.5%) cases were urothelial confined carcinoma (PTa) while 67(55.8%) each accounted for lamina propria (PT1) and only 20 (16.7%) were muscle-invasive carcinoma(PT2). Conclusion: TCC is the most common histopathological type of UBC. Bladder tumors are more commonly encountered in males with the majority of cases occurring in the 6th decade. Both intermediate‐grade TCC in stage (PT1) and low‐grade carcinomas stage (PTa) were relatively common patterns seen in this study